PERSPECTIVES OF THE INTERACTION OF RAILWAY AND AIR TRANSPORT IN THE ASPECT OF DECARBONIZATION AND INTELLECTUALIZATION - BOIKO, SERGEY; VYSHNEVSʹKYY, SVIATOSLAV; POLISHCHUK, PETRO; LAPINA, OLEXANDRA; GVOZDIK, STANISLAV (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Main railway transport occupies an important place in the field of domestic freight and passenger transport. On the other hand, railway transport is a consumer of both fuel and electrical energy. The electrification of main railways brings Ukraine closer to the successful implementation of the program of decarbonization and greening in the field of transport. Meanwhile, the dependence of electrified railway transport on the supply of electrical energy is increasing, which affects the safety of transportation, timeliness and reliability of cargo delivery. In terms of intellectualization, modern digital and telecommunication technologies are being implemented in railway transport, which require reliable and high-quality power supply. For this purpose, a number of scientific studies consider the possibility and make specific proposals regarding the inclusion of sources of distributed generation, including on the basis of renewable sources of electrical energy, in particular wind generators, solar batteries or their hybrid combinations. Such solutions make it possible to ensure a reliable power supply of the responsible electric receivers of the rolling stock, thereby ensuring the reliability of the operation of railway transport. At the same time, new principles of interaction between different types of transport are being actively implemented. One of them is the interaction of railway and air transport. Aviation transport today is represented by manned aircraft and unmanned aerial vehicles. The vision proposed by the authors regarding the improvement of the existing power supply systems in the aspect of decarbonization and intellectualization of the railway infrastructure is aimed at maintaining a sufficiently high level of safe interaction of the railway with other types of transport, including air transport. Increasing the level of safety in railway transport is achieved due to the introduction of new technologies for the purpose of monitoring the state of the railway infrastructure through the introduction of unmanned aerial vehicles.